2002
DOI: 10.1046/j.1365-2141.2002.03749.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylation is an inactivating mechanism of the p16 gene in multiple myeloma associated with high plasma cell proliferation and short survival

Abstract: Summary. In order to gain further insights into the role of the p16 gene in cell cycle regulation and the prognostic implications of its inactivation, we investigated the methylation status of the p16 gene in 98 untreated patients using a polymerase chain reaction assay based on the inability of some restriction enzymes to digest methylated sequences. Forty-one patients showed a p16 methylated gene (42%). The percentage of S-phase plasma cells (PC) in these patients was almost three times higher than in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 36 publications
3
44
3
Order By: Relevance
“…Previous reports have already shown that hypermethylation of p16 is a common phenomenon in MM and MGUS. [6][7][8][9]35 While two studies found a correlation of aberrant p16 methylation with a poorer outcome, 8,9 Guillerm Figure 1 Representative MSP analysis of patient samples. Lanes U: amplified products with primers recognizing the unmethylated gene sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have already shown that hypermethylation of p16 is a common phenomenon in MM and MGUS. [6][7][8][9]35 While two studies found a correlation of aberrant p16 methylation with a poorer outcome, 8,9 Guillerm Figure 1 Representative MSP analysis of patient samples. Lanes U: amplified products with primers recognizing the unmethylated gene sequence.…”
Section: Discussionmentioning
confidence: 99%
“…This epigenetic event acts as an alternative to mutations and deletions to disrupt tumor suppressor gene function. 4,5 It was reported previously that hypermethylation of the cell cycle inhibitors p15 and p16, [6][7][8][9] the apoptosis regulator DAP kinase 10 and the tumor suppressor RASSF1A 11 may occur in MM patients. Additionally, we have recently identified hypermethylation-associated silencing of the suppressor of cytokine signaling-1 (SOCS-1) gene to be a frequent epigenetic aberration in MM.…”
Section: Introductionmentioning
confidence: 99%
“…p16 gene methylation has been considered to be a molecular event associated with the progression of MALT lymphoma to its high-grade counterpart. [15][16][17][18][19] However, our findings suggest that p16 gene methylation is not associated with the tumor progression but rather may contribute to the 35,36 and by the frequent p16 gene methylation found in monoclonal gammopathy of undetermined significance, in the plaque phase of mycosis fungoides, and in other premalignant lesions. [20][21][22]37 Several MALT lymphoma-specific or -associated gene alterations have been reported, such as translocations between the immunoglobulin heavy chain gene and BCL10 gene or MALT1 gene, trisomy 3, and trisomy 18, as well as API2-MALT1 fusion.…”
Section: Discussionmentioning
confidence: 83%
“…10,11 In lymphoid malignancies, p16 gene silencing, mainly induced by gene methylation, is frequently found in Hodgkin and non-Hodgkin lymphomas, [12][13][14] and has been associated with tumor progression. [15][16][17][18][19] However, it has also been suggested that the methylation of this gene is one of the early events in the development of lymphoid malignancies. [20][21][22] MALT lymphoma constitutes more than 80% of all primary lung lymphomas.…”
mentioning
confidence: 99%
“…In other B-cell malignancies, DAPK and p16 gene methylation has been associated with tumor progression. [40][41][42] However, recent studies have shown that methylation of these genes may be an early event in lymphomagenesis: DAPK and p16 gene methylation is frequently found in premalignant and low-grade lymphoid disorders, not associated with tumor progression, and their methylation status is maintained in higher-grade or advanced lymphoid neoplasms. [43][44][45][46][47][48] In line with these findings, methylation of DAPK and p16 is a common, early epigenetic phenomenon that allows tumor cells to promote cellcycle progression and escape the normal apoptosis of a non-antigen-stimulated expanded B-cell population.…”
Section: Primary Cutaneous Marginal Zone B-cell Lymphoma H Takino Et Almentioning
confidence: 99%